Influential variables impacting the reliability of building occupancy sensor systems: A systematic review and expert survey. (25th January 2022) - Chu, Yiyi; Mitra, Debrudra; O'neill, Zheng; Cetin, Kristen
Abstract : Occupancy information is critical for buildings, as it can substantially impact energy consumption. However, occupancy is highly unpredictable, and depends on occupants' schedules and their interactions with building systems. Occupancy sensor systems have been deployed in buildings for many years, using a broad range of sensor types, most typically for lighting control. Similarly, many research studies have been conducted that use a range of sensor modalities for occupancy sensing. These studies have assessed reliability considering diverse variables, testing methods, and evaluation metrics. However, no comprehensive review of occupancy sensor system reliability has been compiled. In this research, a review of the literature on occupancy sensor systems is presented, focusing on influential variables that may cause systems to incorrectly represent occupancy. Next, a survey was developed and completed by researchers, practitioners, and other stakeholders, ranking the most influential variables. The results of this effort provide a tiered list of what both literature and experts suggest are the most influential factors on occupancy sensor system performance. Future work includes the development of a standard methodology to evaluate the reliability of different occupancy sensor systems based on these efforts.